Clinicopathological diagnosis of Lennert lymphoma: a case report and review of the literature - Shun Ding; Jiao Chen; Jiajun Su; Jiewen Liu; Weihua Yin; Fengjie Qi (BMC, 2024)
Abstract Background Lennert lymphoma (LL) is a variant of peripheral T-cell lymphoma, not otherwise specified (PTCL, NOS), also known as a lymphoepithelioid variant of PTCL. Because of the rarity and lack of clear-cut diagnostic criteria, LL is susceptible tomisdiagnosis. Although previously diagnosed with LL might be reclassified and evaluated with the advent of of molecular and/or genetic findings, cytomorphology and immunohistochemistry are still the key to give rise to correct diagnosis. Case presentation We report a case of a patient who was diagnosed as LL based on cytomorphology and immunohistochemistry. Routine stain (Hematoxlin and Eosin-H&E) revealed tumor cells were mainly small to medium-sized CD4(+) T cells, the CD8 +/TIA-1 + cytotoxic cells were less minority, no expressions of follicle helper T cell markers (CD10, BCL6, PD1, CXCL13, ICOS) or CD21(+) hyperplastic FDC network, or proliferation of high edndothelial venules were noted; however, numerous epithelioid histiocytes are noted in the background and scattered EBV(+) cells were also present. The patient was achieved complete remission after six courses of chemotherapy with cyclophosphamide, epirubicin, vincristine, etoposide, and prednisone regimen. She was followed for 5 years without recurrence or progression. Conclusions Classic LL is not difficult to diagnose by cytomorphology and immunohistochemistry, and the mutation profiles can be helpful to distinguish LL from other lymphomas.